ANALISIS DAMPAK PRAKTIK RENTENIR TERHADAP DINAMIKA EKONOMI MASYARAKAT KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Zaenudin; Rully Trihantana; Miftakhul Anwar (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
The needs of human life are increasing along with the increasingly modern era. This is a problem for some people with middle to lower incomes, so the idea came out to run a business, with an easy process and access through debt to loan sharks. In practice, debts to moneylenders are not able to prosper the borrower, because loans from moneylenders are only able to meet their material needs for a moment but not their spiritual needs. This causes it to be difficult for borrowers to pay off debts with such high interest. In Islamic law, this is forbidden because loan sharks take such large profits (interest) or usury. This study aims to determine the impact of moneylender practices on the dynamics of the community's economy, then viewed from the perspective of Islamic law on society, especially the people of Pamijahan District, Bogor Regency. This research is a descriptive qualitative research, and analyzes it deductively. The results obtained in this study are that the impact of moneylender practices on economic dynamics is very detrimental to society, and in an Islamic economic review, loan shark practices are very contrary to Islam because they contain usury. Therefore it is prohibited to carry out loan shark practices.